Awareness of the Association between Periodontal Health and Diabetes Mellitus among Middle-Aged Population in Burridah, Saudi Arabia: Life Sciences-Periodontitis for Dental health - Dr. Alanood Alzogibi; Dr. Fares Al-Shubrumi; Dr. Sumona Bhattacharjee; Dr.Vivek Prabhu (International Journal of Life Science and Pharma Research, 2022)
The link between diabetes mellitus and periodontal diseases has been well-established. But there is a lack of awareness in comparison with other systemic complications. This study aims to assess the awareness of the association between diabetes mellitus and periodontal diseases in a high risk group of population and to identify the important factors which influence this knowledge. The study was a cross sectional survey, which selected 248 individuals. The inclusion criteria were the attendants of Outpatients clinic who were aged = 40 years old, while patients with mental illness were excluded. Data were collected by interviewing patients using a questionnaire with closed-ended questions in three sections. The first section contained questions about characteristics of the study respondents; the second section had questions on clinical examination, and the third section contained questions about knowledge of the effect of diabetes on periodontal health. For sections 1 and 2 of the questionnaire, the descriptive statistics of frequencies and percentages was calculated and presented in frequency distribution tables. The associations between certain demographic and clinical characteristics were presented in crosstabs and the significant differences were detected using chi-square test at 0.05 alpha level of significance. Out of 284 periodontal patients recruited in this study, 67.3% was female and 32.7% was male with majority of the respondents (about 64%) aged 40-50 years old. About 55% had diabetes mellitus and about 66% of them had a family member diagnosed with diabetic mellitus. About 46% of the respondents were aware of the relation between diabetes and gum health. A half of the respondents reported the escalating risk of periodontal diseases among diabetic patients. This awareness was found significantly associated with women of high educational level, positive familial history of diabetes, and number of physician visits. There is lack of awareness of the impact of diabetes on periodontium health in high risk and middle-aged group of general population.